Public health investigation and response to a hepatitis A outbreak from imported scallops consumed raw—Hawaii, 2016. (17th October 2018) - Viray, M. A.; Hofmeister, M. G.; Johnston, D. I.; Krishnasamy, V. P.; Nichols, C.; Foster, M. A.; Balajadia, R.; Wise, M. E.; Manuzak, A.; Lin, Y.; Xia, G.; Basler, C.; et al.
Abstract: During the summer of 2016, the Hawaii Department of Health responded to the second-largest domestic foodborne hepatitis A virus (HAV) outbreak in the post-vaccine era. The epidemiological investigation included case finding and investigation, sequencing of RNA positive clinical specimens, product trace-back and virologic testing and sequencing of HAV RNA from the product. Additionally, an online survey open to all Hawaii residents was conducted to estimate baseline commercial food consumption. We identified 292 confirmed HAV cases, of whom 11 (4%) were possible secondary cases. Seventy-four (25%) were hospitalised and there were two deaths. Among all cases, 94% reported eating at Oahu or Kauai Island branches of Restaurant Chain A, with 86% of those cases reporting raw scallop consumption. In contrast, a food consumption survey conducted during the outbreak indicated 25% of Oahu residents patronised Restaurant Chain A in the 7 weeks before the survey. Product trace-back revealed a single distributor that supplied scallops imported from the Philippines to Restaurant Chain A. Recovery, amplification and sequence comparison of HAV recovered from scallops revealed viral sequences matching those from case-patients. Removal of product from implicated restaurants and vaccination of those potentially exposed led to the cessation of the outbreak. This outbreak further highlights the need for improved imported food safety.